Architectural Renovations of Body-As-Temple. Issue 2 (3rd May 2016) - Carroll, Timothy
Abstract : This paper addresses the Christian religious tradition of understanding the human body as the 'temple of the Holy Spirit' within the context of body modification in Eastern Orthodox Christianity. Drawing on ethnographic research in Jerusalem and Kansas City, interviews with artists and Orthodox Christians, and theological discourses on the body and art, this paper seeks to understand how the body is treated by Orthodox Christians and evaluates the ethical commitments and contestations around the human body and religious practice. The paper focuses specifically on tattooing practices, which, though typically prohibited in conservative forms of Christianity, are nonetheless practiced as a means of devotion in specific Eastern Orthodox Christian settings. These modifications to the body are taken in dialogue with ritual and practical concerns exhibited in Eastern Orthodox burial practice. The paper argues that while there are commonalities across Eastern Orthodox practice, the ethical implications of specific actions are highly contextualized and must be interpreted within local regimes of aesthetic behaviour.